Problems of Oral Translation - Azizbek qizi, Odiljonova Sarvinoz (International Journal of Innovative Analyses and Emerging Technology, 2021)
When you stop and think about it, everything in life is translation. We translate our feelings into actions. When we put anything into words, we translate our thoughts. Every physical action is a translation from one state to another. Translating from one language into another is only the most obvious form of an activity which is perhaps the most common of all human activities. This maybe the reason people usually take translation for granted, as something that does not require any special effort, and at the same time, why translation is so challenging and full of possibilities. There is nothing easy or simple about translation, even as there is nothing easy or simple about any human activity. It only looks easy because you are used to doing it. Anyone who is good at a certain activity can make it appear easy, even though, when we pause to think, we realize there is nothing easy about it.